Dyplomacja naukowa w warunkach skrajnego napięcia między państwami oraz potencjalna rola wulkanów w dyplomacji. Studium przypadku Pektu-san .......... 59 - Dorda, Martyna; Korzonek, Hanna; Trzecina, Wiktor (Oblicza dyplomacji, 2025)
SCIENTIFIC DIPLOMACY IN ATMOSPHERE OF EXTREME TENSION BETWEEN STATES AND THE POTENTIAL OF VOLCANOS IN DIPLOMACY: PEKTU-SAN CASE STUDYThis article focuses on the issue of the new Axis of Evil, i.e. countries such as Russia, Iran and North Korea. It raises the issue of deterrence of these countries using conventional methods and the problems resulting from this. It discusses the danger related to the possession of nuclear weapons by these countries and the necessity of establishing unofficial channels of communication with them in the event of a crisis. The proposed solution is scientific diplomacy. Chosen example of it might be the research project on the Paektu volcano, when Western scientists were invited to North Korea in 2011. The article takes into account the important cultural significance of this place for both Koreas and the danger this volcano poses. It also discusses the Paektu eruption in 946, and the potential problems related to volcanic eruptions today. The course of the research project on the Paektu volcano is described. The guidelines of one of the Western participants regarding cooperation with scientists from an antagonistic country were analyzed, as well as the conditions conducive to a potential increase in the frequency of similar scientific cooperations.